Asynchronous ovarian torsion–the case for prophylactic oophoropexy. Issue 810 (April 1993) - Grunewald, B.; Keating, J.; Brown, S.
Abstract : The case of an 11 year old girl who suffered torsion of the left ovary 8 months following right oophorectomy for a similar event is presented. The left ovary was saved by immediate surgical intervention. The value of prophylactic oophoropexy in unilateral ovarian torsion is discussed.